New genera of Lachesillidae (Psocodea:’Psocoptera’: Eolachesillinae: Graphocaeciliini) from Valle del Cauca, Colombia - Aldrete, Alfonso N. García; Obando, Ranulfo González; Carrejo, Nancy S. (Zootaxa, 2013)
Two new related Colombian genera of Lachesillidae, including three new species, from the Department of Valle del Cauca, are here described and illustrated. They belong in the tribe Graphocaeciliini (Eolachesillinae). The new genera differ from the other genera in the tribe lacking ocelli, by characters of the male clunium, phallosome, endophallus, paraprocts, and female subgenital plate, gonapophyses and IX sternum. The types are deposited in the Entomological Museum of the Universidad del Valle (MUSENUV), in Santiago de Cali, Colombia.